The Church in a Pluralistic World The Public Vision of Ressourcement - Flynn, Gabriel 1960- (2019)
The dual concern of this article is to present the vision of the church articulated by the renowned generation of Catholic ressourcement thinkers in the mid-twentieth century, and to demonstrate its continued fecundity in the pluralist, multi-cultural context of contemporary western society. It seeks to contribute primarily to ecclesiology, while also providing historical and social commentary with respectful suggestions for its relevance to present-day ecclesiology. The article provides an interpretative framework for understanding ressourcement with reference to its philosophical foundations and the vision of its founders. Its aims are, first, to articulate the role of ressourcement in the modern context and, secondly, to document the genesis and emergence of that movement's perception of the church's mandate in the world, based on an essential return to the sources of Christianity. The paper presents the public vision of ressourcement ecclesiology in two parts, drawing principally, though not exclusively, on the work of the two leading intellectual orders of the Catholic Church at the time of its formulation, namely, the Dominicans and the Jesuits of France. In this paper, I limit myself to the French-speaking Jesuits and Dominicans and do not refer to Rahner, Semmelroth, Schillebeeckx or Schoonenberg.
Keywords: Chenu; Congar; Fourvière; Saulchoir; De Lubac; Pluralism; public vision; Ressourcement; Secularization